Bioefficacy of Eugenol-Based Bioinsecticide from Clove Leaf Oil (Syzygium aromaticum) against Brown Planthopper (Nilaparvata lugens) - Edy Cahyono; Cindy Maharani; Saffanah Binti Mohd Ab Azid; Samuel Budi Wardhana Kusuma; Dyah Rini Indriyanti; Prayogo Probo Asmoro; Ridho Prasetyo (Biosaintifika: Journal of Biology & Biology Education, 2026)
The brown planthopper (Nilaparvata lugens) is one of the most destructive pests of rice, causing significant yield losses and threatening global food security. The extensive use of synthetic insecticides has led to environmental concerns and the development of insecticide resistance, highlighting the need for sustainable alternatives. This study aimed to purify eugenol from clove leaf oil (Syzygium aromaticum), formulate a stable oil-in-water bioinsecticide emulsion, and evaluate its insecticidal and antifeedant activities against N. lugens. Eugenol was enriched through vacuum fractional distillation and characterized using GC-MS, GC, FTIR, and physicochemical analyses. The purified eugenol was subsequently formulated using Tween 80 and ethanol, and its biological activity was assessed through toxicity and honeydew excretion bioassays. Vacuum fractional distillation increased eugenol content from 53.53% to 94.30%. Clove oil and purified eugenol exhibited LC50 values of 0.016% and 0.019%, respectively. In definitive toxicity assays, clove oil caused 90.00% mortality at 0.120%, whereas purified eugenol produced 73.33% mortality at 0.076% after 96 h of exposure. In addition, purified eugenol reduced feeding activity by up to 60%, demonstrating pronounced antifeedant effects. These findings indicate that eugenol contributes to both lethal and sublethal suppression of N. lugens and highlight the potential of clove-derived bioinsecticides as environmentally compatible alternatives for sustainable rice pest management. The study further provides a value-added strategy for utilizing clove leaf oil and contributes to the development of SDG 2 (Zero Hunger), SDG 12 (Responsible Consumption and Production), and SDG 15 (Life on Land).